Race and digital media an introduction - Lopez, Lori Kido (Cambridge, [England] Polity Press, 2023)
This textbook provides a comprehensive introduction to the theory and research on race and digital media. Focusing on the experiences of people of color in the United States, it explores the various ways that racism and white supremacy have shaped aspects of our digital world -- from the infrastructures and policies that support technological development, to algorithms and the collection of data, to the interfaces that shape engagement. Yet it also reveals how communities of color have deployed digital media in ways that expand the public sphere, contest the status quo, and give voice to creativity and joy. --Back cover.
Introduction -- The early internet -- Labor -- Infrastructures -- Artificial intelligence -- Surveillance -- Tech policy -- Activism -- Games -- Communities -- Into the future.
Includes bibliographical references (pages [198]-222) and index.
Keywords: Digital media -- Social aspects -- United States; Racism -- United States